Effect of sucrose on the functional composition and antioxidant capacity of buckwheat (Fagopyrum esculentum M.) sprouts. (April 2018) - Jeong, Hyejin; Sung, Jeehye; Yang, Jinwoo; Kim, Younghwa; Jeong, Heon Sang; Lee, Junsoo
Highlights: Sucrose was used as an elicitor during buckwheat sprout germination. Sucrose treatment increased bioactive compounds of buckwheat sprout. Sucrose treatment increased tyrosine and phenylalanine ammonia-lyase activities. Buckwheat sprouts treated with sucrose modulated antioxidant enzyme activity in HepG2 cells. Abstract: In this study, the effects of sucrose on nutritional and functional composition as well as antioxidant activities in buckwheat sprouts during germination were investigated. Treatment with 1%, 2%, or 3% sucrose resulted in an increase in the amount of vitamins, four C -glycosylflavones, and rutin. Tocopherols and β-carotene in sprouts treated with 1%, 2%, and 3% sucrose were increased in a dose-dependent manner. Similarly, the sum of individual flavonoid was 1.35, 1.29, and 1.60 times higher than that of control sprouts. Sucrose treatment increased tyrosine and phenylalanine ammonia-lyase activities resulting in an increase in the flavonoid content. Moreover, treatment of HepG2 cells with buckwheat sprouts ameliorated oxidative damages by modulating reactive oxygen species production, malondialdehyde generation, and antioxidant enzyme activities. These results suggest that sucrose treatment could improve the nutritional composition and antioxidant effects of germinating buckwheat sprouts.